Impact of the anodization time on the photocatalytic activity of TiO2 nanotubes - Díaz-Real, Jesús A.; Dubed-Bandomo, Geyla C.; Galindo-de-la-Rosa, Juan; Arriaga, Luis G.; Ledesma-García, Janet; Alonso-Vante, Nicolas (Beilstein Journal of Nanotechnology, 2018)
Titanium oxide nanotubes (TNTs) were anodically grown in ethylene glycol electrolyte. The influence of the anodization time on their physicochemical and photoelectrochemical properties was evaluated. Concomitant with the anodization time, the NT length, fluorine content, and capacitance of the space charge region increased, affecting the opto-electronic properties (bandgap, bathochromic shift, band-edge position) and surface hydrophilicity of TiO2 NTs. These properties are at the origin of the photocatalytic activity (PCA), as proved with the photooxidation of methylene blue.
Keywords: fluorine doping; nanotubes; photocatalytic activity; photoelectrochemistry; titanium(IV) oxide (TiO2)